이앙직전 벼 육묘상자 살포용 완효성 비료의 처리 효과 - 지정현; Jeong-hyun Chi; 최병열; Byoung-rourl Choi; 조광래; Gwang-lae Jo; 김순재; Soon-jae Kim; 박경열; Kyeong-yeol Park; 권오연; O-youn Kwon (Korean journal of crop science, 2013)
The newly developed fertilizer is the slow-releasing fertilizer which can be used as a basal fertilizer without no additional fertilization at tillering stage. It has 30-4-6% of N-P 2 O 5 -K 2 O and was coated with mixture of LDPE (Low density polyethylene), EVA (Ethylene vinyl acetate), BDP (Bio degraded polymer), TALC and nonionic surfactant for the controlled release up to 50 days after application. Coating materials were designed to be decomposed naturally. This fertilizer can be applied directly to the seedling tray mechanically just before transplanting, resulting in significant labor saving effect. The developed slow-release fertilizer, which can replace both basal fertilization and top dressing at tillering stage by single application directly to seedling tray, showed the highest release at 14～21 days after transplanting. Considering the plant growth at different growth stages and yield, the optimal application rate of developed slow-release fertilizer was 300 g per rice nursery tray and the yield of rice at this application rate was 5.25 MT/ha. Rice quality in terms of head rice grain ratio, amylose content, whiteness, and taste value decreased as fertilization rate increased from 200 g to 500 g per nursery tray. Fertilization rate based on quantity of fertilizer ingredients (N, P, K) was reduced by 49.3% compared to the standard application rate and there was 49.2% reduction in labor input for fertilization.